Residual cholangiopathy: stadistical study - Deschamps, Jorge H (Cirugía del Uruguay, 1978)
The author of this analysis o'f residual cholangiopathies defines them as disorders which appear or re appear somme time after surgery of the biliary tract. Case material involves 79 operations due to "residual cholangiopathies", out of a total of 2. 000 operations of biliary tract. The papel includes a statistical analysis o'f this series.